LEXICAL TYPOLOGY IN NUSANTARA FABLES - Sarah Nasution (Jurnal Dialect, 2025)
This study explores the lexical typology of Indonesian fables, examining the linguistic features that contribute to their narrative structure and cultural meaning. This research focuses on the use of motion verbs which are part of the lexical typology and analyzes how these literary devices convey moral lessons and cultural values. This research uses a qualitative method by analyzing a collection of Indonesian fables from various regions. This chapter identifies the most common lexical typological characteristics, including the movement verbs contained in them. Research findings show that many movement verbs in Indonesian fables convey moral lessons and cultural values. Idioms are also commonly used to add humour and cultural nuance to stories. This research aims to demonstrate the importance of lexical typology in understanding the narrative structure and cultural meaning of Indonesian fables, providing insight for linguists, anthropologists and educators interested in Indonesia's cultural heritage